2008
DOI: 10.1016/j.ultsonch.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical preparation of SbSI gel

Abstract: A novel sonochemical method for direct preparation of nanocrystalline antimony sulfoiodide (SbSI) has been established. The SbSI gel was synthesized using elemental Sb, S and I in the presence of ethanol under ultrasonic irradiation (35 kHz, 2 W/cm2) at 50 degrees C for 2 h. The products were characterized by using techniques such as powder X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), high-resolution transmission electron microscopy (HRTEM), selected are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
70
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 39 publications
13
70
0
3
Order By: Relevance
“…Using the method presented in Nowak et al (2009a), the energy gap of SbSI in the composite was determined. Value of this energy gap E g = 1.835(23) eV is in good agreement with results presented previously for SbSI (Nowak et al 2008). For wavelengths higher than 700 nm, the presence of cellulose fibers causes monotonous decrease of cellulose/SbSI reflectance coefficient.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Using the method presented in Nowak et al (2009a), the energy gap of SbSI in the composite was determined. Value of this energy gap E g = 1.835(23) eV is in good agreement with results presented previously for SbSI (Nowak et al 2008). For wavelengths higher than 700 nm, the presence of cellulose fibers causes monotonous decrease of cellulose/SbSI reflectance coefficient.…”
Section: Resultssupporting
confidence: 91%
“…Characterization of the SbSI gel was accomplished using other techniques, such as X-ray powder diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and selected area electron diffraction (SAED). The equipment and procedures were the same as presented by Nowak et al (2008Nowak et al ( , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The surface area of the sonochemically prepared SbSI is about 75 m 2 /g [6]. It is consistent with the SEM observations (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This material has large surface-to-volume ratio. It was found that SbSI nanocrystals amounts only 4.7% of the xerogel volume [6].…”
Section: Introductionmentioning
confidence: 99%
“…Other less common techniques, such as sonochemical synthesis 126,127,162,122 and electrophoretic deposition 71 , have also been employed for the 75 synthesis of ferroelectric nanowires and nanorods. Ramesh et al 163,164 introduced the concept of focussed ion beam (FIB) milling for the 'top-down' fabrication of ferroelectric nanostructures.…”
Section: Template-free Synthesis Of 1d Nanoferroelectricsmentioning
confidence: 99%